(untitled) (International Journal of Engineering and Computer Science, 2018)
- The Photovoltaic (PV) sources are more compatible for Microgrids because of their ability to internally aggregate and balance with other renewable sources. The conventional grid connected PV inverters are basically current source controlled so unable to control ac voltage or frequency. The PV inverter using the Consortium for Electric Reliability Technology Solutions (CERTS) concepts can control ac voltage and frequency but have a major problem with load transients. The over loaded PV micro source causes dc bus voltage collapse and finally resulting in an ac voltage drop during the load transients. A photovoltaic inverter is capable of operating in both island and grid-connected mode by means of a reconfigurable control scheme. This paper presents an efficient control strategy which causes the PV inverter to act as voltage source to maintain stable dc bus voltage under load transients. With this PV inverter control configuration, it is shown that the PV micro source can operate as a voltage source in the CERTS microgrid.